Management of chronic non-communicable diseases in Ghana: a qualitative study using the chronic care model - Hubert Amu; Eugene Kofuor Maafo Darteh; Elvis Enowbeyang Tarkang; Akwasi Kumi-Kyereme (BMC, 2021)
Abstract Background While the burden and mortality from chronic non-communicable diseases (CNCDs) have reached epidemic proportions in sub-Saharan Africa (SSA), decision-makers and individuals still consider CNCDs to be infrequent and, therefore, do not pay the needed attention to their management. We, therefore, explored the practices and challenges associated with the management of CNCDs by patients and health professionals. Methods This was a qualitative study among 82 CNCD patients and 30 health professionals. Face-to-face in-depth interviews were used in collecting data from the participants. Data collected were analysed using thematic analysis. Results Experiences of health professionals regarding CNCD management practices involved general assessments such as education of patients, and specific practices based on type and stage of CNCDs presented. Patients' experiences mainly centred on self-management practices which comprised self-restrictions, exercise, and the use of anthropometric equipment to monitor health status at home. Inadequate logistics, work-related stress due to heavy workload, poor utility supply, and financial incapability of patients to afford the cost of managing their conditions were challenges that militated against the effective management of CNCDs. Conclusions A myriad of challenges inhibits the effective management of CNCDs. To accelerate progress towards meeting the Sustainable Development Goal 3 on reducing premature mortality from CNCDs, the Ghana Health Service and management of the respective hospitals should ensure improved utility supply, adequate staff motivation, and regular in-service training. A chronic care management policy should also be implemented in addition to the review of the country's National Health Insurance Scheme (NHIS) by the Ministry of Health and the National Health Insurance Authority to cover the management of all CNCDs.